Combining Transcriptome and Hormone-Targeted Metabolome Analyses to Dissect the Regulatory Mechanisms Underlying Wheat Peduncle Elongation - Huifang Hao; Lu Chen; Zhiyang Cao; Xiujuan Jin; Feng Guo; Zerui Shi; Jinwen Yang; Juan Lu; Daizhen Sun (Plants)
Wheat is an important global food crop. The peduncle significantly impacts the plant’s height, architecture, and yield, and understanding its genetic mechanisms is crucial not only for improving wheat’s architecture but also for enhancing its yield. In this study, we identified an elongated uppermost internode (eui) mutant in the EMS-induced progeny of Jinmai 90 (JM90). We conducted phenotypic identification, genetic analysis, and cytological observation combined with transcriptome and targeted hormone metabolism analysis and compared the differences between the eui mutant and the wild-type (WT). The results indicated that an incompletely dominant gene mutation caused the eui mutant to display significant elongation of the peduncle and an increase in the plant height. This was attributed to the considerable elongation of parenchyma cells, while no significant differences were noted in other internodes. These traits were accompanied by an increase in the spikelets per spike and grains per spike. Subsequently, transcriptome and targeted hormone metabolome sequencing were performed and identified 15,969 differentially expressed genes (DEGs) and 27 hormone-related differentially accumulated metabolites (DAMs). KEGG enrichment analysis indicated that the DEGs in MS1_VS_WS1 were significantly enriched in two pathways: those related to tryptophan metabolism and diterpenoid biosynthesis. Analysis indicated that the peduncle elongation caused by the eui mutant is primarily regulated by auxin. This study offers a foundation for the exploration and cloning of genes associated with the peduncle, establishing a theoretical basis for understanding the molecular mechanisms behind wheat peduncle elongation and for developing ideal plant types and breeding high-yield varieties.